2018
DOI: 10.17507/jltr.0902.01
|View full text |Cite
|
Sign up to set email alerts
|

English as a Tool to Prevent Bullying and Encourage Equalities: The KiVa Project

Abstract: Abstract-Through the combination of the KiVa project and the English language beyond its formal academic aspects, this work aims to achieve an efficient antibullying program that fits the students' needs. The main objective of this research is to prevent bullying, to encourage equalities and to ensure that bullying victims can count on the support of the class group to feel more confident about themselves and to not be afraid. To carry out all this, we suggest using English as students' L2 in order that it ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…The English language might be considered as a tool to create Altruism among students by reflecting, discussing, sharing ideas and feelings. Furthermore, somebody who is good at English is able not only to read and write in English, but he/she is also able to interpret the social situations (Jimenez & Diaz, 2018).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The English language might be considered as a tool to create Altruism among students by reflecting, discussing, sharing ideas and feelings. Furthermore, somebody who is good at English is able not only to read and write in English, but he/she is also able to interpret the social situations (Jimenez & Diaz, 2018).…”
mentioning
confidence: 99%
“…Drawing upon those phenomena, there had been some studies intended to be conducted in terms of altruism praxis in English classroom, such as Jimenez & Diaz (2018) found that English language is considered as a tool to create anti bullying attitudes among students. English is chosen as the subject since it is a neutral common language for all the students.…”
mentioning
confidence: 99%